Analisis Hukum Islam Terhadap Tabungan Emas di Bank Syariah: Kajian Fikih dan Ceramah Buya Yahya - Dwi Mutiara Sarie; Fadli Aziz; Siti Naurah (Dirosah Islamiyah: Jurnal Studi Islam, 2026)
This study aims to analyze the legal status of gold savings in Islamic banks from the perspective of Islamic jurisprudence (fiqh muamalah), with a focus on the concept of riba, particularly riba yad, and by relating it to the views of classical and contemporary scholars. The method used is qualitative research with a library research approach and content analysis of YouTube lectures by Buya Yahya. The data sources are derived from classical fiqh books such as At-Taqrirat as-Sadidah, Nihayatul Maqashid, and Bidayatul Mujtahid.The results of the study show that gold is classified as a ribawi commodity whose transactions must fulfill the principle of taqabudh (immediate possession) in order to avoid riba yad. Classical scholars strictly prohibit any delay in gold transactions, while some contemporary scholars provide limited flexibility under the conditions of clear contracts and definite ownership. However, based on the analysis of Buya Yahya’s lectures, digital gold savings that do not involve actual possession and transfer are generally rejected due to their potential to contain elements of riba yad. Therefore, gold savings practices must be carefully examined to ensure compliance with Islamic principles.